LA PUESTA EN VALOR DEL MANTO BLANCO DE PARACAS: UN PROYECTO DE GESTIÓN DE UN PATRIMONIO CULTURAL SANMARQUINO - Franco Torres, César Augusto (2017)
In 2016 the Museo de Arqueología y Antropología de San Marcos and the Centro Cultural inaugurated, on the occasion of the 465th anniversary of the University, the museographic exhibition: “ Sala Paracas: Vientos del Sur “, which meant the recovery and valorization of the White Mantle of Paracas, an asset of our university, unique in its kind, for its peculiar characteristics, both of manufacturing and decorative.